Functional clinical typology of the foot and kinematic gait parameters - Jitka Marenčáková; Zdeněk Svoboda; Ivan Vařeka; František Zahálka (Palacký University Olomouc, 2016)
Background: The foot plays a key role in a standing posture, walking and running performance. Changes in its structure or function may alter upper segments of kinematic chain which can lead to formation of musculoskeletal disorders. Although functional clinical typology provides a complex view of foot kinesiology there is a lack of knowledge and evidence about influences of different foot types on human gait. Objective: The aim of the study was to analyse differences of kinematic gait parameters of lower extremity joints and pelvis between functional clinical foot types in healthy young men. Methods: Three-dimensional kinematic analysis by the Vicon Motion Capture MX System device in synchronization with 2 Kistler force platforms was used to obtain kinematic data from 18 healthy men (mean age 23.2 ± 1.9 years). The functional clinical foot type was clinically examined and sorted into 3 basic foot type groups - forefoot varus (FFvar), rearfoot varus (RFvar) and forefoot valgus (FFvalg). Peak angular values and range of an angular displacement in all of three movement planes were analysed for pelvis, hip, knee and ankle joint. For statistical analysis of kinematic gait parameters differences between foot types Mann Whitney U test at a statistical significance level p < .05 and Cohen's coefficient d for effect size were used. Results: This study showed that functional clinical foot type can affect kinematic parameters of gait in the joints of the lower limb and pelvis. Significant differences were presented in the FFvar in comparison with other two foot type groups with middle and high size of effect. The most alterations were observed in pelvis area and in a sagittal plane of movement. Nevertheless, significant differences between FFvalg and RFvar foot types were not noticed. Conclusions: Functional clinical foot typology provides one of the possible methods to describe foot structure and function. Our results showed that foot type could alter gait. Forefoot varus foot type has more significant influence on kinematic gait parameters then other foot types. These effects should be considered by clinicians during examination of musculoskeletal system disorders especially in lower extremities.